DEVELOPING PREZI NEXT AS TEACHING MEDIA OF RECOUNT TEXT FOR EIGHTH GRADE OF JUNIOR HIGH SCHOOL - Ari Tata Pratama; Nora Ronita Dewi (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
The aim of this stuy was to develop writing speaking through media for eightth grade of Junior High School Student in SMP Swasta Panca Abdi Binjai. By using Research & Development design with six stages, they were Gathering Information and Data, Analyzing Data, Material Design, Validating by Experts, Revising, and Final Product. With 30 individuals responses as the data subjects through Interviews and Questionnaires. From the material, the first validator scored 75,8% of excellent, and the score from the second validator was 82,8%, and it was categorized as relevant. And from the media, 52% from the first validator, and 50% of the highest score from the second. In means that the media were valid and appropriate to use as learning media for students. The results of the product was Prezi Next as the presentation and learning online media for those individuals. Later on, the media was test using Recount Text as the measurement of the media to these subjects. This also leads to attractive media which introduced to help them motivated and keep interested. Thus, the media were valid and appropriate to use as learning media for students.Keywords: Prezi Next, Recount Text, Research and Development.